Reggie, penguin in charge - Oliveira, Jen de (Little Brown Ink, an imprint of Little, Brown and Company, 2024)
Reginald "Reggie" Guinn is a playful kid penguin who gets into everyday adventures at school, home, and his neighborhood.
Ages 4-8
Accelerated Reader AR
Keywords: Penguins -- Fiction; Graphic novels; Graphic novels